Etnisyyden rakentuminen kahden saamelaismuseon perusnäyttelyissä - Potinkara, Nika (University of Jyväskylä, 2015)
This study examines the construction of ethnicity in the permanent exhibitions of two museums: Siida, the National Museum of the Finnish Sámi and the Nature Centre of Metsähallitus, and Ájtte, the Swedish Mountain and Sámi Museum. The study is motivated by three research questions: What kind of ethnic categories and boundaries do the exhibitions create? How is Sámi ethnicity defined by displaying cultural features? How do the exhibitions depict relationships between the Sámi and other ethnicities, governmental power, the ‘Sámi area’, and nature? The exhibitions are examined in the context of the contemporary public discussion about Sámi ethnicity; the study aims to explain how the two museums, by presenting Sámi culture and history, contribute to this discussion. The theoretical framework of the study is based on a constructionist view of ethnicity, which assumes that ethnic boundaries are maintained by a limited set of cultural features. The primary data of the study consist of the permanent exhibitions of Siida and Ájtte which were first put on display between the years 1989–2005, and were studied by the author during the period 2009–2012. The exhibitions were analyzed qualitatively within the theoretical and methodological framework of discourse analysis. The secondary data include several exhibitions on Sámi culture in other museums, a variety of media materials reflecting contemporary discussions and debates about Sámi ethnicity, and interviews with museum staff. The findings of the study suggest that the two museums, with a few possible exceptions, tend to produce a clear and stable ethnic boundary between the Sámi and other ethnicities. Most of the established symbols of Sámi ethnicity, occurring frequently in the public discussion about the Sámi, serve to signify the ethnic boundary in the museums as well. The Sámi are represented as one of the northern indigenous peoples, living in the ‘Sámi area’ and being closely connected to nature. The exhibitions of Siida and Ájtte thus resemble the images produced by the Sámi movement, emphasizing the unity and togetherness of the Sámi people rather than cultural or social heterogeneity within Sámi societies.